Real-world efficacy and safety of first-line nivolumab plus chemotherapy in patients with advanced gastric, gastroesophageal junction, and esophageal adenocarcinoma: A nationwide observational Turkish Oncology Group (TOG) study - Kutlu, Yasin; Dae, Shute Ailia; Yılmaz, Feride; Erdem, Dilek; Şendur, Mehmet Ali Nahit; Akbaş, Sinem; Şenocak Taşçı, Elif; Baş, Onur; Dane, Faysal; Sakin, Abdullah; Kaya, Ali Osman; Aykan, Musa Barış; et al. (My University, 2024)
Based on the CheckMate 649 trial, nivolumab plus chemotherapy is the recommended first-line treatment for HER2-negative unresectable advanced or metastatic gastric, gastroesophageal junction (GEJ), or esophageal adenocarcinoma. This nationwide, multicenter, retrospective study evaluated the real-world effectiveness of this regimen in Turkish patients and identified subgroups that may experience superior outcomes. Conducted across 16 oncology centers in Turkey, this study retrospectively reviewed the clinical charts of adult patients diagnosed with HER2-negative unresectable advanced or metastatic gastric, GEJ, or esophageal adenocarcinoma from 2016 to 2023. This study included 111 patients (54 women, 57 men) with a median age of 58 years. The median progression-free survival (PFS) and overall survival (OS) were 11.7 months and 18.2 months, respectively, whereas the objective response rate (ORR) was 70.3%. Multivariable analyses revealed that previous curative surgery was a favorable independent prognostic factor for both PFS and OS. Conversely, an Eastern Cooperative Oncology Group performance status of 2 emerged as an adverse independent prognostic factor for OS. The safety profile of nivolumab plus chemotherapy was found to be manageable. Our findings support the use of nivolumab plus chemotherapy for the first-line treatment of Turkish patients with HER2-negative unresectable advanced or metastatic gastric, GEJ, or esophageal adenocarcinoma. Patient selection based on clinical characteristics is crucial for optimizing treatment outcomes.
Keywords: Chemotherapy; Efficacy; Gastric Adenocarcinoma; Nivolumab; Real-World; Safety